Three-dimensional visualized space and asset management system for large-scale airports: The case of Incheon International Airport. (September 2016) - Kim, Eonyong; Park, Soohoon
Large-scale airports such as Incheon International Airport have large-scale terminals, annex buildings, and numerous open spaces. An integrated space management system is required to manage these buildings and spaces efficiently. Thus, Incheon International Airport Corporation developed a three-dimensional computer-aided design–based integrated space management system. The major system development goal was to provide intuitive three-dimensional-based visual information, thereby realizing an integrated space and asset management system that does not require expert knowledge of any specific field, such as architecture. This article discusses the construction of the system and the problems that had to be resolved to achieve this goal.